Kepercayaan Konsumen Kafe ditinjau dari Halal Life Style Di Kota Jambi (Studi Kasus Pada Kesiko, Eat & Fun dan Clave Cafe) - Subhan Subhan (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2020)
This paper aims to describe the influences of halal lifestyle towards cafes’ customer trust in Jambi City. This paper used qualitative research methods based on primary and secondary data. Study cases are taken from Kesiko, Eat & Fun and Clave Cafe, they were chosen because of their popularity and business duration. The sampling method is snowball sampling with 50 respondents from customers and managers and staff at Kesiko Eat and Fun Cafe and Clave Cafe. The results of this study indicate that the halal lifestyle has been quite well implemented in Kesiko, Eat and Fun Cafe and Clave Cafe in Jambi City. it evidenced by the role of cafe management, sellers, and customers who carry out their activities based on the indicators of halal lifestyle, such as food and beverages before selling must be considered as halal food and drinks or has been labeled halal.